Equal Substitution of Synthetic Nitrogen Fertilizer with Azolla Compost on Growth, Yield, and Nitrate Content of Green Onion in Ultisols - Chiristiana; Marwanto; Marlin; Handajaningsih, Merakati; Anggraini, Septiana (Akta Agrosia, 2023)
The impact of Azolla compost (AC) substitution for synthetic N fertilizer (NF) on nitrate leaf content and agronomic performances of green onion in Ultisols have not been well understood. Therefore, this study aimed to assess the effects of equal replacing NF with AC on growth, yield, and nitrate accumulation in the green onion leaf. The polybag trial was performed in June 2020 on the crop research farm of the Agriculture Faculty in a completely randomized design with six treatments in five replications. Green onion was subjected to five 92 kg ha−1 N equal combinations of NF and AC, i.e., NF100 (100% NF+0% AC), NF75 +AC25 (75% NF+25% AC), NF50 +AC50 (50% NF+50% AC), NF25 +AC75 (25% NF+75% AC), and NF0 +AC100 (0% NF+100 % AC) and no NF and AC as a control. Results demonstrated that NF+AC treatments significantly improved plant height, leaf number, tiller number, stem diameter, and plant fresh weight. Treatment of NF25+AC75 resulted in similar responses to the recommended dose of N fertilizer, as evidenced by plant height, number of green leaves, root fresh weight, shoot dry weight, tiller numbers per hill, stem diameter, shoot fresh weight, and plant fresh weight. Lower leaf nitrate contents occurred under increased substitution of NF with AC. Thus, partial substitution of NF with AC could be a sustainable option for improving growth and yield while reducing nitrate accumulation in the leaf of green onion in Ultisols. Keywords: azolla compost substitution, integrated nutrient management, synthetic fertilizer reduction,  green onion agronomic performance, Ultisols Keywords: azolla compost, green onion, integrated nutrient management, chemical fertilizer reduction,  Ultisols